Порогове резонансне двофотонне народження e−e+ пари в сильному магнiтному полi на найнижчi рiвнi Ландау - Dyachenko, M. M.; Novak, O. P.; Kholodov, R. I. (Publishing house "Academperiodika", 2018)
The process of electron-positron pair production by two photons in a strong magnetic field has been studied. The process kinematics is considered, and the probability amplitude for arbitrary polarizations of particles is found. The resonance conditions are established, and the resonant cross-section is estimated in the case where the electron and the positron occupy the lowest levels (le = 1, lp = 0) that satisfy these resonance conditions.